Danish teleophthalmology platform reduces optometry referrals into the national eye care system. Issue 1 (18th March 2021) - Muttuvelu, Danson Vasanthan; Buchholt, Heidi; Nygaard, Mads; Rasmussen, Marie Louise Roed; Sim, Dawn
Abstract : Objective: The purpose of this study was to evaluate the stratification of follow-up and referral pathways after implementation of a systematic cloud-based electronic-referral teleophthalmological service for optometry-initiated ocular posterior segment disease referrals to the Danish national eye care system. Methods and Analysis: A retrospective cohort study was conducted in the period from 1 August 2018 to 31 July 2019. Patients with suspected ocular posterior segment disease reviewed by the telemedical ophthalmology service were included. The service stratified patients into the categories: no need for follow-up, follow-up by optometrist, follow-up by the telemedical service and referral to the national Danish eye care service. Results: From a pool of 386 361 customers, 9938 patients were enrolled into this study. 19.5% of all patients were referred to the Danish national eye care system, while 80.5% of the patients in the telemedical service were not, in the period from 1 August 2018 to 31 July 2019. 14.4% of the optometrist referrals did not need any follow-up, while a majority of 66.1% needed some follow-up either by the optometrist themselves or within the telemedical service. Conclusion: Optometrist posterior segment disease referrals can be considerably reduced with a risk stratified approach and optimal use of technology. New models can improve and streamline the healthcare system.